The Dominance of the Agency Model on Financing Decisions - Bramantyo Djohanputro (Gadjah Mada International Journal of Business, 2015)
There are some issues about how companies consider their financing. These issues are related to the amount, source, type, and the structure of such financing. So far, there is no uniform model that is able to explain how companies deal with these issues. There are three competing, dominant theories of financing decision making, i.e. the Pecking Order Theory, the Static Trade-off Theory, and the Agency Model Theory. This study attempts to explore which theory explains the best way for companies in the consumer industry to decide their financing method. There are five hypotheses to be tested in this study. Using data from public listed companies on the Indonesian Stock Exchange from 2008 to 2011, it seems that the Agency Model Theory is more dominant than the other two theories in explaining the way companies fulfill their financing needs.